ANÁLISIS HIDROGEOQUÍMICO DE LA CALIDAD DE AGUAS SUPERFICIALES EN UNA ZONA MINERA EN EL FLANCO OESTE DE LA CORDILLERA OCCIDENTAL DE LOS ANDES - Quispe Vargas, Alexis Junior (2023)
This study used the hydrogeochemical properties of surface waters surrounding a mining project in Peru to compare them with the environmental quality standards established in Supreme Decree 004-2017-MINAM, focusing on category 3 for vegetable irrigation and animal drinking. Physical-chemical, inorganic, microbiological and parasitic parameters were evaluated in lagoons and springs. The results determined the presence of slightly alkaline deposits with a pH of 9.59 and slightly acidic deposits with a pH of 5.33, as well as deposits with high content of iron, manganese, and zinc. To ensure the reliability of the chemical analysis, an ionic balance of the main dissolved cations and anions was performed. The Piper diagram determined the predominant calcic sulfate waters, as well as the presence of a calcic bicarbonate water deposit. On the other hand, the Stiff diagram determined sulfate (SO42-) as the predominant ion. This study concludes that the different stations comply with the environmental quality standards, although deposits with high levels of iron, manganese, and zinc were found in surface waters. Different treatments were determined to control pH levels and to decrease the amount of such ions present.